Pancasila Philosophical Values as the Regulation Basis of Intellectual Property Rights In Indonesia - Usmina Wijaya, Andy; Ayumeida Kusnadi, Sekaring (KnE Social Sciences, 2023)
Not only having recognition of property rights, the customs and culture of Indonesians also have a social function. As the strongest legal standing, intellectual property rights are individualistic to monopolize ownership rights over intellectual works. This right is developed in individualistic and capitalistic countries. Pancasila as the nation’s philosophy is more prioritizing the balance between rights and social functions, therefore the regime of intellectual property rights is different from the characteristics of Indonesia. Pancasila contains values for the soul of the nation and the ideals of Indonesia law. Pancasila recognizes intellectual property rights as part of the legal ideals to achieve the national goals, i.e creating public welfare. It also contains fundamental basic values that must cover the regulations, including those related to intellectual property rights. By this reason, it is necessary to develop a basis in theory and practice to balance rights and social function that reflect Pancasila as the philosophy of Indonesia people, including to limit and to exclude exclusive rights. Keywords: Intellectual property Rights, Pancasila; Indonesia